Accelerated Corneal Collagen Cross-Linking in Pediatric Patients: Two-Year Follow-Up Results. (10th September 2014) - Shetty, Rohit; Nagaraja, Harsha; Jayadev, Chaitra; Pahuja, Natasha Kishore; Kurian Kummelil, Mathew; Nuijts, Rudy M. M. A.
Abstract : Purpose. To evaluate the effectiveness and safety of accelerated corneal collagen cross-linking (ACXL) in patients below 14 years of age with progressive keratoconus. Materials and Methods . Thirty eyes of 18 patients with established progressive keratoconus underwent preoperative and postoperative visual acuity assessment, topography, and specular microscopy prior to ACXL and were followed up for 24 months. Results. Mean age of the patients was 12.7 years with ten males and eight females. There was an improvement in the mean postoperative uncorrected distant visual acuity (from 0.76 ± 0.26 to 0.61 ± 0.25 ; P = 0.005 ), mean corrected distant visual acuity (from 0.24 ± 0.19 to 0.12 ± 0.12 ; P < 0.001 ), mean spherical refraction (from - 3.04   DS ± 3.60 to - 2.38   DS ± 3.37 ; P = 0.28 ), mean cylinder (from - 3.63   DC ± 1.82 to - 2.80   DC ± 1.48 ; P = 0.008 ), and spherical equivalent (from - 4.70   D ± 3.86 to - 3.75   D ± 3.49 ; P = 0.15 ). Three eyes of two patients with vernal keratoconjunctivitis (VKC) showed progression. There were no intra- or postoperative complications. Conclusion. In pediatric patients ACXL is an effective and safe procedure for the management of keratoconus. Optimal management of VKC is important to arrest the progression of keratoconus.